Effect of submucosal injection in endoscopic papillectomy of ampullary tumor: Propensity‐score matching analysis. Issue 4 (1st May 2018) - Chung, Kwang Hyun; Lee, Sang Hyub; Choi, Jin Ho; Kang, Jinwoo; Paik, Woo Hyun; Ahn, Dong-Won; Ryu, Ji Kon; Kim, Yong-Tae
Abstract : Background: The role of submucosal injection (SI) in endoscopic papillectomy (EP) is controversial. Objective: This study investigated the effects of SI before EP of ampullary tumors. Methods: All patients who underwent initial curative EP at our institution between March 2006 and March 2014 were retrospectively recruited. The presence of residual tumor after three months, recurrence‐free survival and post‐procedural adverse events were compared between the SI group and non‐injection (NI) group. Propensity‐score matching was performed between the two groups to reduce potential selection bias and confounding. Results: A total of 122 patients were included (SI: 26, NI: 96). Following propensity‐score matching, 25 paired patients were selected. Residual tumor was not shown in the NI group, whereas seven (28.0%) patients in the SI group had residual tumor ( p  = 0.010). The recurrence‐free survival of the NI group was significantly longer than that of the SI group ( p  = 0.036). Upon multivariate analysis, pathologic grade ( p  = 0.026) and SI ( p  = 0.033) were significantly related to recurrence‐free survival. Post‐procedural adverse events were not significantly different between the two groups. Conclusion: SI before EP of ampullary tumor was related to more frequent residual tumor and shorter recurrence‐free survival and did not reduce post‐procedural adverse events.